Hiperaldosteronismo primário felino: Uma enfermidade endócrina emergente - Bento, Daniel Diola; Zahn, Fabíola Soares [UNESP]; Duarte, Laura Carolina; Machado, Luiz Henrique de Araújo [UNESP] (FapUNIFESP (SciELO), 2016)
The primary hyperaldosteronism, an endocrine disease increasingly identified in cats, is characterized by adrenal gland dysfunction that interferes with the renin-angiotensin- aldosterone system, triggering the hypersecretion of aldosterone. Pathophysiological consequences of excessive aldosterone secretion are related to increased sodium and water retention, and increased excretion of potassium, which induce hypertension and severe hypokalemia, respectively. The most common clinical findings in cats include: polydipsia, nocturia, polyuria, generalized weakness, neck ventroflexion, syncope, anorexia, weight loss, pendulous abdomen and blindness. Diagnosis is based on the evidence of hormonal hypersecretion with suppression of renin release, imaging and histopathological evaluation of adrenal glands. Treatment may be curative with adrenalectomy, in cases of unilateral disease, or conservative, through administration of aldosterone antagonists, potassium supplementation and antihypertensives. Prognosis varies from fair to good with the appropriate therapy. This article reviews the main aspects of primary aldosteronism in cats, providing the clinician with important information for the diagnosis of this disease.
Feline primary hyperaldosteronism: An emerging endocrine disease
Keywords: Adrenocortical disease; Endocrinology; Feline medicine; Hypertension